Analisis Kepatuhan terhadap Penerapan Kode Etik Profesi Akuntan Publik di Indonesia (Jurnal Kendali Akuntansi, 2025)
The purpose of this study is to analyze how Indonesian public accountants comply with their code of ethics. The researcher uses a qualitative approach to collect data for this study, by referring to various scientific publications, papers, journals, and other sources. However, the author's data collection method is a literature study methodology. The subjects of this study are public accountants of the Indonesian Public Accounting Office. According to the research findings, in order to maintain public trust, the code of ethics of the public accountant profession must be adhered to. In addition, by implementing a code of ethics, an accountant is seen as more professional, reliable and trustworthy. An accountant must be independent because a lack of independence can violate the basic principles of ethics regarding the objectivity of an auditor in working.